The Development of Sensitivity to Grammatical Violations in American Sign Language: Native Versus Nonnative Signers. Issue 4 (5th June 2017) - Novogrodsky, Rama; Henner, Jon; Caldwell‐Harris, Catherine; Hoffmeister, Robert
Abstract: Factors influencing native and nonnative signers' syntactic judgment ability in American Sign Language (ASL) were explored for 421 deaf students aged 7;6–18;5. Predictors for syntactic knowledge were chronological age, age of entering a school for the deaf, gender, and additional learning disabilities. Mixed‐effects linear modeling analysis revealed main effects of each predictor and an interaction between signing status and learning disability. The native signers showed typical syntactic development that varied by chronological age, gender, additional learning disabilities, and age of entering a deaf school. In contrast, the syntactic development of nonnative signers was more variable. It was less tightly related to chronological age and more strongly influenced by the age at which they had entered the school where assessment occurred, which was highly related to length of exposure to a sign language.